A Qualitative Study of Midlevel Nurse Managers' Perspectives of Scholarly Inquiry. (14th March 2023) - Lombardo, Mary Jo; Vioral, Anna; Ley, Cathaleen; Alderfer, Mary Ellen; Mackay, Periwinkle; Kverno, Karan; Milburn, Rowena Leong; Hohl, Dawn; Lindauer, Cathleen; Gerstenhaber, Melissa
Abstract : OBJECTIVE: This study explored the key characteristics and needs of midlevel nurse managers (MLNMs) who support and engage clinical nurses (CNs) in scholarly inquiry. BACKGROUND: Healthcare organizations expect CNs to participate in scholarly inquiry, incorporating evidence-based interventions to improve outcomes and safety. How the MLNM supports and engages CNs in scholarly inquiry remains unclear. METHODS: Twelve semistructured interviews of MLNMs occurred at several facilities in the mid-Atlantic region utilizing the institutional review board–acknowledged protocol. Theme interpretation utilized inductive analysis. RESULTS: Four recurrent themes emerged from the interviews related to the value of scholarly inquiry: 1) securing organizational resources to promote scholarly inquiry; 2) knowledge and experience in scholarly inquiry; 3) actions supporting scholarly inquiry; and 4) the value of scholarly inquiry within the organization. CONCLUSIONS: Senior nursing leadership and healthcare organizations must recognize the value and provide the infrastructure to support scholarly inquiry. Infrastructure includes education, dedicated time, access to expertise, and resources.